PERAN EFEKTIF CORPORATE GOVERNANCE ATAS TAX AVOIDANCE PADA SEKTOR PERTAMBANGAN - Yolanda Margareta; Ratna Septiyanti; Niken Kusumawardani (Faculty of Economics and Business, 2022)
This reseacrh aims to examine the correlation between corporate governance and tax avoidance and how effective corporate governance is in tax avoidance in mining companies listed on Indonesia Stock Exchange. By using purposive sampling in the observation periode 2010-2019, obtained 234 observations from 40 mining companies listed on Indonesia Stock Exchange. Data were analyzed by using descriptive statistics and for hypothesis testing using Spearman's non-parametric analysis to the elements of corporate governance and tax avoidance. This results of this study show that the elements of corporate governance that consist of audit committee meetings and audit quality have negative and significant correlation with tax avoidance as measured using Cash Effective Tax Rate (CETR). Other result shows that institutional ownership has negative and insignificant correlation with tax avoidance, and independent commissioner has positive and insignificant correlation with tax avoidance.